Critical Review of KMA 1503/2025: The Transformation of the Madrasah Curriculum Based on Deep Learning and the Curriculum of Love - Ahmad Suryadi; Abdul Azis Masang; Muhammad Ulil Amri; Samikshya Madhukullya; Emmanuel Ande Ivorgba (Yayasan Azhar Amanaa Yogyakarta, 2026)
This article analyzes the implementation of KMA Number 1503 of 2025 as a strategic policy that reconstructs the direction of madrasah curriculum development through two main pillars: Deep Learning (PM) and Love-Based Curriculum (KBC). This policy marks a fundamental paradigm shift, where madrasahs are no longer positioned as centralized curriculum implementers, but as institutions that have broad autonomy in designing, adjusting, and contextualizing the curriculum according to the needs of students and local characteristics. This autonomy provides space for madrasahs to develop program differentiation and optimize local content as a vehicle for forming essential competencies and strengthening learner identity. Deep learning emphasizes a meaningful, reflective learning process oriented towards critical, collaborative, and creative thinking skills, while KBC focuses on the formation of values, affections, and moderate character based on compassion, respect, and humanity. The integration of the two is aimed at producing a graduate profile that is intellectually intelligent, religious, and has an inclusive character. The results of the analysis show that the successful implementation of KMA 1503/2025 is strongly influenced by madrasah readiness in facing the demands of managerial transformation, strengthening teacher capacity, and fulfilling adequate learning resources. These factors are important prerequisites for the principles of Deep Learning and KBC to be applied consistently and effectively in the classroom. This article recommends the need for systemic support through teacher training, curriculum implementation assistance, and reorganization of madrasah management to align with the new policy direction. Thus, KMA 1503/2025 has great potential to strengthen the quality of madrasah education while affirming the role of madrasah as a center of learning that is humanist, transformative, and responsive to change.